How nutrition-friendly are agriculture and health policies in Bangladesh? - Naher, Firdousi; Barkat-e-Khuda; Ahmed, Shaikh Shamsuddin; Hossain, Mahabub (SAGE Publications, 2014)
The improvements in nutrition status in Bangladesh, particularly child nutrition outcomes, have been relatively slow, despite remarkable improvements in the country's food situation as well as in the health sector. At present more than 40% of children under 5 years of age are stunted.To examine the specific food, agriculture, and health policies that have existed and currently exist in Bangladesh from the perspective of nutrition and identify gaps in the policy framework for which improvements in nutrition have been slow.Policy documents, public financial and budget documents, and related papers were reviewed. Several interviews with former civil servants and bureaucrats were conducted.The approach to achieving food security has been a partial one, with policy provisions focusing excessively on increasing the availability of food, primarily rice. The “accessibility” pillar of food security has received little attention, while the neglect of the “utilization” pillar is conspicuous by the dearth of appropriate policies and laws for ensuring food safety. The efforts in the health sector have largely concentrated on expanding the coverage of primary healthcare, with little consideration of equity and quality.There exists a wide window of unexplored opportunity to align the remarkable increases in food production and advances in the health sector with nutrition considerations toward an improved nutrition status in Bangladesh.